Crowdfunding and religiosity : an understanding of the dynamics of religiosity on social lending in Kiva - Pinto, Manuela Vanessa Gonçalves (2013)
This dissertation aims to study the discrepancy between academic research and laboratory studies regarding the relationship between the religiosity level of an individual and its engagement with pro-social activities. This study examined the hypothesis that religiosity, spirituality and/or altruistic values would display a pro-social behaviour on on-line micro-lending. A survey of 3928 individuals from the Crowdfunding platform Kiva.org contributed to the understanding of the relationship between religiosity and pro-social behaviour on on-line platforms. Findings in this setting indicate that non-religious individuals display a higher engagement level with online pro-social activities on Kiva than do religious or spiritual individuals. Discussion focused on the discrepancy between in-group and out-group affiliation within religious individuals (different values), as well as feminine and non-feminine targets. This has clear implications for micro-lending platform owners, consumer behaviour, marketing segmentation and targeting of online users.